KINERJA KARYAWAN: PERAN KEADILAN DISTRIBUTIF, KESELAMATAN KESEHATAN KERJA (K3) DAN BURNOUT: STUDI KASUS PADA KARYAWAN DEPO JAKARTA - Sisca Triamanda Mutiara; Didin Hikmah Perkasa; Muhammad Al Faruq Abdullah; Wenny Desty Febrian; Setiyo Purwanto (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to determine the effect of Distributive Justice, Occupational Health and Safety (OHS), and Burnout on employee performance at Depot in Jakarta. The research design is descriptive quantitative. The population consists of 100 employees of the Depot in Jakarta. The sample for this study is also 100 employees, using the saturation sampling method, where all employees are included as samples. The data analysis technique used in this study is SEM PLS (Partial Least Square). The first stage of making research instruments, distributing questionnaires and processing data. The second stage examines the effect of each variable of distributive justice, occupational health and safety (OHS), and burnout on employee performance. The results showed that the distributive justice variable had an effect on employee performance, the occupational health and safety (OHS) variable had an effect on employee performance, and the burnout variable had an effect on employee performance at Container Depot in North Jakarta